2020
DOI: 10.3390/cells9051071
|View full text |Cite
|
Sign up to set email alerts
|

PAI1 is a Marker of Bad Prognosis in Rectal Cancer but Predicts a Better Response to Treatment with PIM Inhibitor AZD1208

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide. The standard treatment in locally advanced rectal cancer is preoperative radiation alone or in combination with chemotherapy, followed by adjuvant chemotherapy. Rectal cancer is highly lethal, with only 20% of patients showing a complete remission (by RECIST) after standard treatment, although they commonly show local or systemic relapse likely due to its late detection and high chemotherapy resistance, among other reasons. Here, we explored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Accumulating evidence has suggested that PAI-1 contributed to tumor cell proliferation, migration, invasion, drug resistance and epithelial-mesenchymal transition (EMT), and that high PAI-1 protein expression was associated with unfavorable biological behavior and patient prognosis in HCC ( 19 , 21 , 22 ). Therefore, the present study selected PAI-1 for subsequent functional analysis and investigated the roles of PAI-1 in TAM(CAF).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Accumulating evidence has suggested that PAI-1 contributed to tumor cell proliferation, migration, invasion, drug resistance and epithelial-mesenchymal transition (EMT), and that high PAI-1 protein expression was associated with unfavorable biological behavior and patient prognosis in HCC ( 19 , 21 , 22 ). Therefore, the present study selected PAI-1 for subsequent functional analysis and investigated the roles of PAI-1 in TAM(CAF).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study revealed that lactate secreted by HCC and PDAC cells stimulated the M2 phenotypic transformation of macrophages and enhanced VEGF expression by nuclear factor erythroid 2-related factor 2 (NRF2) activation, and that M2 macrophages triggered NRF2 signaling activation in cancer cells via paracrine VEGF, thereby promoting EMT ( 6 ). Several previous studies have shown that PAI-1 contributed to cell invasion and migration by mediating EMT in colorectal cancer ( 19 ), gastric adenocarcinoma ( 48 ) and non-small cell lung cancer ( 49 ). Furthermore, the present results demonstrated that E-cadherin protein expression level was downregulated, while N-cadherin, Snail and Twist1 protein expression levels were upregulated in the Huh-7 treated with TAM(CAF), and these effects were reversed by the inhibition of PAI-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SERPINE1 has been widely known to regulate the progression of numerous cancers, which highlights the application of SERPINE1 as a potential target. 9,10 We validated that SERPINE1 was remarkably correlated with macrophage infiltrations and the EMT of OS. Knocking down SERPINE1 by si-SERPINE1 could decrease CAFs infiltration and activity, and inhibit OS progression via inducing M1 macrophage polarisation (Figure 4).…”
mentioning
confidence: 74%